1985
DOI: 10.1021/bi00335a046
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of gelsolin and gelsolin-actin complexes with actin. Effects of calcium on actin nucleation, filament severing, and end blocking

Abstract: Gelsolin is a calcium binding protein that shortens actin filaments. This effect occurs in the presence but not in the absence of micromolar calcium ion concentrations and is partially reversed following removal of calcium ions. Once two actin molecules have bound to gelsolin in solutions containing Ca2+, one of the actins remains bound following chelation of calcium, so that the reversal of gelsolin's effect cannot be accounted for simply by its dissociation from the ends of the shortened filaments to allow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
1

Year Published

1986
1986
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 33 publications
12
138
1
Order By: Relevance
“…80% of the bound gelsolin was pelleted a second time in EGTA, compared to 94% in calcium. Janmey et al [33] have reported that actin filaments capped with macrophage gelsolin also showed incomplete dissociation of the gelsolin when calcium was removed. This is not surprising in view of the very tight association between the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…80% of the bound gelsolin was pelleted a second time in EGTA, compared to 94% in calcium. Janmey et al [33] have reported that actin filaments capped with macrophage gelsolin also showed incomplete dissociation of the gelsolin when calcium was removed. This is not surprising in view of the very tight association between the two proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The nucleating and severing activities are calcium dependent, but removal of calcium does not reverse all actin binding [3-51. For example, only one monomer dissociates from the ternary complex, leaving a binary complex containing trapped calcium, which cannot be dissociated without denaturation [3]. Similar properties have been reported for gelsolins from a variety of sources, including rabbit macrophage [6], human plasma [7] and pig stomach smooth muscle [8]. In contrast, pig plasma gelsolin has been shown to interact with actin both in the presence and absence of calcium [9-111.…”
Section: Introductionmentioning
confidence: 87%
“…Purification of cytoplasmic gelsolins has conventionally been carried out in the presence of EGTA (to prevent interaction with cellular actin) [6], while plasma gelsolin has been purified by affinity chromatography on actin-Sepharose in the presence of calcium [14] (blood plasma contains about 2 mM calcium). Cytoplasmic gelsolin-actin complexes have also been purified in the presence of calcium by affinity chromatography on DNase I-agarose [ 151, but subsequent separation of the complexes in 6 M urea was done in 1 mM EGTA [3].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, villin functions as a bundling protein and does not sever actin filaments (anmey and Matsudaira, 1988;Petrucci et al, 1988); gCap39 binding to actin is reversible by Ca++ chelation and has limited ability to sever filaments (Southwick and DiNubile, 1986;Young et al, 1990;Yu et al, 1990). In contrast, gelsolin severs actin filaments, caps the barbed-end of filaments, and is not dissociated from actin by Ca++ chelation but only by exposure to PIP2 micelles (Janmey et al, 1985Janmey and Matsudaira, 1988). Because villin is not found in platelets or PMNs, because [Ca++]i is "tonically" elevated (for .5 min) (Sullivan et al, 1989) in FMLP activated PMN, and because ligand activation causes both Ca++ transient and PIP2 turnover (Pozzan et al, 1983;Cockcroft et al, 1985;Lapetina, 1990;Stephens et al, 1991), we investigated the role of gelsolin as a plausible regulator and creator of barbed-end nuclei in FMLP activated neutrophils.…”
Section: Ga Interactions In Basal Etf-pmnsmentioning
confidence: 99%
“…Interactions of gelsolin with actin in vitro are regulated by Ca++ and PIP2 (Yin and Stossel, 1979;Yin et al, 1981b;Janmey et al, 1985. In vitro micromolar Ca++ activates gelsolin's ability to sever filamentous (F) actin, cap the barbed (+) end of F-actin, and nucleate globular (G) actin polymerization at the pointed end of the filament.…”
Section: Introductionmentioning
confidence: 99%